IOS CoreAudio developer talks - Adamson, Chris (Addison-Wesley Proffesional, 2013)
"IOS Core Audio LiveLessons (Developer Talks) provides real-world training on the basics of working with iOS Core Audio in an easily accessible, presentation-style format. Bestselling author and iOS expert Chris Adamson offers novice programmers practical advice on how (and when) to work with the iOS Core Audio framework along with hands-on, step-by-step video training. This presentation does not assume any previous experience working with Core audio and you'll be able to put his examples to use easily and effectively in your own iOS application development."--Resource description page.